Filmi Boža Škerlja - Križnar, Naško (Traditiones (Ljubljana), 2005)
Božo Škerlj was the first anthropologist in former Yugoslavia with Ph.D., while it is not known to everybody that he also practiced amateur filmmaking. In the 30's and 40's of past century he filmed the family life and the scenes of his working activity. 24 film units are preserved which total duration is 90 minutes. In the article the history and a character of his filmmaking is presented, the content of the films and their significance for the study of culture as well.
Keywords: Škerlj, Božo, 1904-1961; biografije; ethnology; etnologija; vizualna antropologija; amaterski filmi; vizualna kultura; Slovenia; Slovenija; zgodovinski pregledi